Comparison of Airborne Electromagnetic and Ground-based Resistivity Observations: Case Study Banda Aceh Basin. Issue 1 (October 2021) - Irwandi, I; Syafrizal,; Rifqan,; Naufal, H.; Siemon, B.
Abstract: Airborne measurements are very useful to cover very large areas. Nine month after the Aceh Tsunami and Earthquake in 2004, BGR (Federal Institute for Geoscience and Natural Resources) conducted a fresh water supply exploration survey within a project called Helicopter Project Aceh (HELP ACEH). The helicopter-borne electromagnetic (HEM) device operates at five frequencies. The HEM can estimate the 1D resistivity models down to a depth of 150 m for the high electrical resistivity areas and 50 m for low electrical resistivity areas. In this paper, the airborne data of 2005 are compared with resistivity data acquired in Banda Aceh basin in 2018. The HEM output consists of 1D resistivity models derived by inversion of the processed data. These 1D resistivity models are compared with the 2D resistivity models derived from ground-based resistivity measurements. However, the 2D models on the ground are transformed into 1D resistivity models so it can be used for comparison. The transformation is conducted by averaging the resistivity values in the each layer, so every layer only has one resistivity value. Both methods are influenced by many factors. For example, resistivity on the ground is affected by local conditions. The airborne measurements are also influenced by objects that are at the surface of the ground. In some cases, the airborne resistivity models have some differences in absolute resistivity values, but they often have the same structural pattern compared with the ground-based resistivity models.